Pengaruh Kepemilikkan Manajerial, Ukuran Perusahaan, Perisai Pajak Non Hutang, dan Leverage Operasi terhadap Struktur Modal - Putri Salsabila; Mayar Afriyenti (Universitas Negeri Padang, 2022)
This research aims to analyze the effect of managerial ownership,firm size, non debt tax shield and operating leverage on capital structure. This research uses a quantitative approach with a causal associative research type. The data used in this study are annual reports of sector manufacturing listed on the Indonesia Stock Exchange in 2017-2020. Using purposive sampling method we obtained by 272 sample from 68 companies conducted observations from 2017 – 2020. This research using multiple linear regression analysis on the hypothesis testing. The result showed that the managerial ownership, firm size, and operating leverage has a negative and significant effect on capital structure. However, the non-debt tax shield variable has no effect on the capital structure.